The implementation and evaluation of ANP/CNS-led nursing grand rounds in an Irish teaching hospital - Mc Brien, Barry (My University, 2025)
Background: Nursing grand rounds (NGR) is a popular continuing professional development (CPD) resource led by advanced practice nurses. There is a dearth of knowledge on the impact on those who attend NGR in Ireland. Aim: This service analysis aimed to evaluate who attended NGR in one Irish hospital and the impact, if any, on attendees. Methods: A 10-item survey consisting of Likert scale questions was completed by 110 participants, a response rate of 18%. Findings: The majority of the attendees were student nurses (29%) and advanced nurse practitioners (or candidates) (19%), with staff nurse attendance low at 3%. Attendees showed positive impacts on the understanding of different nursing roles, nursing knowledge and nursing collaboration. Conclusion: This evaluation of the impact of NGR on attendees indicates a positive level of education, knowledge, potential collaboration, nurse manager support, and is evidence of nursing leadership in CPD provision. Further research is required to ascertain reasons for poor staff nurse attendance at NGR.
PUBLISHED
Keywords: Nursing grand rounds; Role expansion; Collaboration; Clinical nurse specialist; Advanced nurse practitioner; Leadership in nursing; Nursing; Nursing Education; Other; Education